Reviravolta identitária : um estudo sobre o processo de reconhecimento étnico de Bastiões, Iracema-CE - Marques, José da Guia (2019)
This dissertation analyzes the process of identity and territorial demand of the Bastiões community, located in the rural area of the municipality of Iracema, in the Jaguaribe Valley region, in the state of Ceará, 304 km from Fortaleza. By declining recognition as a remnant quilombo community, this community has renounced its ethnic and territorial rights to which it would have access, based on Article 68 of the Transitional Constitutional Provisions Act (ADCT) of the 1988 Federal Constitution. The aim is to verify the reason why and how the process of renunciation of this identity demand and the corresponding territorial rights occurred, and to what extent the rigidity and uniformity of quilombola legislation, as well as the state intervention through its agents, contributed for the community's abandonment of its identity and territorial demand.